103 Prostate specific antigen utilization trends in an academic hospital in argentina. (20th August 2018) - Martínez, Cintia; Vietto, Valeria; Terrasa, Sergio; Kopitowski, Karin
Abstract : Objectives: To describe trends in Prostate specific antigen determinations, between 2006 and 2015, in men without prostate cancer aged 40 to 79 years who were affiliated to a Health Maintenance Organization associated to an Academic Hospital in Buenos Aires, and their eventual temporary association with US Preventive Services Task Force (USPSTF) recommendations changes during 2008 and 2012. Method: We analyzed a time series of aggregated data. We calculated the annual age standardized rates of accumulated determinations of Prostate specific antigen for every 1 00 000 affiliates without a personal history of prostate cancer. Additionally, we compared trends by age groups (40–49, 50–59, 60–69 and 70–79). We used Jointpoint and MS Excel. Results: We identified 103, 038 Prostate specific antigen determinations performed over a total of 7 84 180 men during the ten year span of the study. Between 2006 and 2008 there was a upward trend in the number of Prostate specific antigen measurements with an annual average percentage increase of +4.4% (95% CI +1.8 to+7.1). Between 2008 and 2011, the curve reached a plateau (−0.3%, −2.6 to +2.3), after which the annual number of determinations began to decrease (annual average reduction of −3.7% (-4.4 to −2.9)). We did not find significant changes between different age groups over those years. Conclusions: We found a gradual decrease in Prostate specific antigen utilization in men between 40 and 79 years affiliated to an Health Maintenance Organization in Buenos Aires after the 2012 USPSTF recommendation against prostate cancer screening.